Electric charge quantization and the muon anomalous magnetic moment - Pires, C. A.D.S. [UNESP]; Rodrigues da Silva, P. S. [UNESP] (American Physical Society (APS), 2002)
We investigate some proposals to solve the electric charge quantization puzzle that simultaneously explain the recent measured deviation on the muon anomalous magnetic moment. For this we assess extensions of the electro-weak standard model spanning modifications on the scalar sector only. It is interesting to verify that one can have modest extensions which easily account for the solution for both problems.